Er det mig, der er problemet? - Pedersen, Louise; Knudsen, Martin Pors (Psyke & Logos, 2015)
When a university student with one or more mental disorders experience educational difficulties, we are presented with a very complex process where the student attempts to manage a great many demands, bonds and opportunities at once. The main thesis of this article is that we need to develop a holistic framework for understanding educational difficulties where these are not reduced to linear effects of diagnosed mental disorders. In this article such a framework is presented with roots in the activity theoretical analysis and concepts of A. N. Leontjev. Furthermore, three structuring tools are presented to be used by educational counsellors for conversations with students, the aim being to understand the complex systemic characteristics of the difficulties and being able to address these. The article is based on individual counselling of students at the team of pedagogical-psychological educational counselling, Aarhus University.